Cali’s food systems: A diagnostic synthesis to determine priority action areas for sustainable food systems - Aronson, Sandra (International Center for Tropical Agriculture, 2019)
Food systems are complex and dynamic, and their governance and planning directly affect food security and nutritional outcomes across urban, peri-urban, and rural communities. The production, consumption, and disposal of food has profound effects on economic development, environmental sustainability, and public health. Among food systems, these three domains have important linkages and synergies which are conveyed through public goods and public policy. Identifying the components that make up food systems can be challenging, especially for decision makers who need to understand how changing individual components in the system may have broader implications on food security and public health. Without robust, generalizable data to explain the interconnectedness between these domains, policymakers cannot make evidence-based recommendations that foster sustainable practices. Thus, policymakers need decision support tools to identify specific problem and sites of action to develop sustainable solutions. This project compares the 44 Monitoring Framework Indicators from the Milan Urban Food Policy Pact (MUFPP) to existing indicators in Santiago de Cali’s Municipal Development Plan and other governmental reports to measure the city’s progress integrating sustainability in its food systems. The MUFPP is a non-binding international protocol aimed at tackling food- related issues at the urban level by having cities share best practices and monitor their progress towards achieving more sustainable foods systems. Preliminary results observed eight indicators that were measured, twenty-five indicators required review or fine tuning, and eleven indicators were missing altogether, pointing to gaps in data and knowledge and potential food system failures. Based on these gaps, a criteria and methodology were developed to determine priority action areas to improve and encourage the use of sustainable practices. (**includes results from methodology**) Cali is not a MUFPP signatory city, change tense but given the upcoming municipal and departmental elections, this rudimentary food systems assessment is an opportunity to present evidence and engage Cali’s decision makers and researchers as they develop future political and research agendas related to food security, environmental protection, and economic development.